Analisis Pesan Dakwah dalam Novel Religi - Rina Rina; Erfian Syah; AD Kusumaningtyas (Muttaqien, 2022)
Da'wah currently can no longer be done in a simple way, the da'wah actors must be able to create their da'wah messages so that the da'wah messages presented can be of interest to the object of their da'wah. Online media are da'wah media that have strong penetration capabilities and high actuality advantages in attracting the object of their da'wah. The purpose of this study was to find out how the objective reality, symbolic reality, and subjective reality of the Al Bahjah Assembly Da'wah Team in Bandung. The type of research used is qualitative research with case study methods. Data obtained through observation, interviews and documentation. The data analysis was carried out by categorizing and reducing data, the data was grouped in the form of narratives, data interpretation, conclusion drawing and verification of the results of data analysis. The conclusions of this study are 1) The objective reality of Al Bahjah's da'wah team is based on the construction of objective reality in accordance with the facts and da'wah messages presented using online media and is based on breakthroughs by cadre of da'i who have multi-skill abilities in both technology and economics. 2) The symbolic reality of Al Bahjah's da'wah team is based on indicators of the creation of da'wah messages. 3) The subjective reality of Al Bahjah's da'wah team lies in the da'wah method through the formulation of the development of online media. The preparation of da'wah planning is carried out systematically, starting from mapping the situation, mapping the object of da'wah and classifying the message of da'wah.